The Effect of Rail Fastening System Modifications on Tram Traffic Noise and Vibration - Stjepan Lakušić; Ivo Haladin; Maja Ahac (Shock and Vibration)
Tram system is a backbone of public transportation in the City of Zagreb. In the last decade, its fleet has been renewed by 142 new low-floor trams. Shortly after their introduction, it was observed that they have a negative impact on the exploitation behavior of tram infrastructure, primarily on the durability of rail fastening systems. Because of that, it was decided to modify existing rail fastening systems to the new track exploitation conditions. When the (re)construction of tram infrastructure is carried out by applying new systems and technologies, it is necessary to take into account their impact on the future propagation of noise and vibration in the environment. This paper gives a short overview of the characteristics of the two newly developed rail fastening systems for Zagreb tram tracks, their application in construction of experimental track section, and performance and comparison of noise and vibration measurements results. Measured data on track vibrations and noise occurring during passage of the tram vehicles is analyzed in terms of track decay rates and equivalent noise levels of passing referent vehicle. Vibroacoustic performance of new fastening systems is evaluated and compared to referent fastening system, in order to investigate their ability to absorb vibration energy induced by tram operation and to reduce noise emission.